Arabidopsis INOSITOL TRANSPORTER2 mediates H+ symport of different inositol epimers and derivatives across the plasma membrane. - Schneider, Sabine; Schneidereit, Alexander; Udvardi, Patrick; Hammes, Ulrich; Gramann, Monika; Dietrich, Petra; Sauer, Norbert (Plant Physiology, 2007)
Of the four genes of the Arabidopsis (Arabidopsis thaliana) INOSITOL TRANSPORTER family (AtINT family) so far only AtINT4 has been described. Here we present the characterization of AtINT2 and AtINT3. cDNA sequencing revealed that the AtINT3 gene is incorrectly spliced and encodes a truncated protein of only 182 amino acids with four transmembrane helices. In contrast, AtINT2 codes for a functional transporter. AtINT2 localization in the plasma membrane was demonstrated by transient expression of an AtINT2-GREEN FLUORESCENT PROTEIN fusion in Arabidopsis and tobacco (Nicotiana tabacum) epidermis cells and in Arabidopsis protoplasts. Its functional and kinetic properties were determined by expression in yeast (Saccharomyces cerevisiae) cells and Xenopus laevis oocytes. Expression of AtINT2 in a Deltaitr1 (inositol uptake)/Deltaino1 (inositol biosynthesis) double mutant of bakers' yeast complemented the deficiency of this mutant to grow on low concentrations of myoinositol. In oocytes, AtINT2 mediated the symport of H(+) and several inositol epimers, such as myoinositol, scylloinositol, d-chiroinositol, and mucoinositol. The preference for individual epimers differed from that found for AtINT4. Moreover, AtINT2 has a lower affinity for myoinositol (K(m) = 0.7-1.0 mm) than AtINT4 (K(m) = 0.24 mm), and the K(m) is slightly voltage dependent, which was not observed for AtINT4. Organ and tissue specificity of AtINT2 expression was analyzed in AtINT2 promoter/reporter gene plants and showed weak expression in the anther tapetum, the vasculature, and the leaf mesophyll. A T-DNA insertion line (Atint2.1) and an Atint2.1/Atint4.2 double mutant were analyzed under different growth conditions. The physiological roles of AtINT2 are discussed.